Of Humans, Forests, and Belonging: A Comparative Reading of Bibhutibhushan Bandyopadhyay’s আরণ্যক (Aranyak; Of the Forest) and Dhoniram Toto’s ধানুয়া ট াট ার কথামালা (Dhanua Totor Kothamal) - Mitu, Nabila Haque (The Jahangirnagar Review Part-C, 2026)
This research explores the human-nature relationship in Aranyak (1939) by Bibhutibhushan Bandyopadhyay and Dhanua Toto’r Kathamala (2021) by Dhanua Toto, focusing on cultural and ethical perspectives of environmental degradation and ecocide. Aranyak presents nature through a romanticized lens, depicting the forest as an untouched paradise. At the same time, Dhanua Toto’r Kathamala offers an indigenous perspective, viewing the forest as sacred and integral to the community’s existence. Both novels critique the destruction of forests by human activity, highlighting the consequences of deforestation, ecocide, and human encroachment. Drawing on ecocriticism and terrapsychology, the study analyzes how these works depict the psychological and cultural impacts of environmental loss. The research emphasizes the ethical imperative to recognize the spiritual and cultural significance of nature for indigenous people. It warns against the dangers of exploiting the environment for short-term gain. Through a comparative approach, this study underscores the role of literature in critiquing ecological destruction and advocating for environmental preservation.